(untitled) - Williams, John; Giacchino, Michael; Whitaker, Forest; Jiang, Wen; Jones, James Earl; Smits, Jimmy; 1963-; 1932-; 1971-; Dillon, Glyn; Crossman, Dave; Chiang, Doug; et al. (Buena Vista Home Entertainment, Inc., 2017)
In a period of great conflict, a group of unlikely heroes led by Jyn Erso, a daring fugitive, and Cassian Andor, a rebel spy, band together on a desperate mission to steal the plans to the Death Star, the Empires ultimate weapon of destruction.
Keywords: Vader, Darth; (Fictitious character); Drama; Drama; Good and evil; Drama; Government, Resistance to; Space warfare; Space vehicles; Drama; Drama; Films for people with visual disabilities; Films for the hearing impaired; Feature films; Fiction films; Action and adventure films; Science fiction films